2021
DOI: 10.1097/cce.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in Coronavirus Disease 2019-Related Critical Illness: A Propensity Matched Analysis

Abstract: Objectives: The primary objective was to evaluate ICU mortality at 28 days in patients with severe hypoxemic respiratory failure due to coronavirus disease 2019 infection who received tocilizumab. The secondary objectives were to evaluate ICU-, hospital-, mechanical ventilation-, and vasopressor-free days at day 28 and development of secondary infections. Design: Retrospective, observational, multicenter, cohort study between March 15, 2020, and May 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
4
11
0
Order By: Relevance
“…Our primary outcome of no difference in microbial isolation rate was observed after adjusting for possible co-founders. This finding is similar to the results of previous studies that conducted adjusted matched analyses for tocilizumab and controls and showed no difference between the groups [ 24 , 25 ]. This was also demonstrated in another multicenter cohort study of 4485 adults with COVID-19 admitted to ICUs and a recent meta-analysis that found no differences in secondary infection rate between tocilizumab and the control group [ 5 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our primary outcome of no difference in microbial isolation rate was observed after adjusting for possible co-founders. This finding is similar to the results of previous studies that conducted adjusted matched analyses for tocilizumab and controls and showed no difference between the groups [ 24 , 25 ]. This was also demonstrated in another multicenter cohort study of 4485 adults with COVID-19 admitted to ICUs and a recent meta-analysis that found no differences in secondary infection rate between tocilizumab and the control group [ 5 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our primary outcomes ndings were observed after adjusting for the patient's comorbidities, history of hospitalization or invasive procedure within one year, history of antibiotics exposure in the last three months, systemic corticosteroids during ICU, and ICU LOS. The nding of no difference in secondary infections rate is similar to previous studies that conducted adjusted matched analyses for tocilizumab and controls and showed no difference between the arms only (26 in the treatment arm, 25 in the control arm; 95% CI for difference, − 0.15 to 0.13; P = 1.00) (20,21). This was also demonstrated in another multicenter cohort study of 4485 adults with COVID-19 admitted to (ICUs) has found no differences in secondary infection rate (140 [32.3%] vs 1085 [31.1%]) (22,23 ).…”
Section: Discussionsupporting
confidence: 87%
“…But Tcz’s effects over critically-ill patients could not be correctly assessed as we found few clinical files of patients with such condition. However, the administration of Tcz at the LIS and/or in doses of > 800 mg seemed to prolong hospitalization, which may be in line with data describing an enhanced propensity for Tcz-treated patients to develop the aforementioned nosocomial superinfections 23 , and thus to present a prolonged stay at intensive care units 25 . We lack bacterial culture data from our patients as a means to confirm this hypothesis, but it seems plausible and we think that further investigation on the prophylactic use of antibiotics to avoid prolonged hospitalization in Tcz-treated COVID-19 patients would help to clarify such point.…”
Section: Discussionsupporting
confidence: 81%
“…Due to the fact that IL-6 is highly expressed in the severe to critical presentations of COVID-19 5 , many research teams have used Tocilizumab (Tcz), a humanized monoclonal antibody that targets the IL-6 receptor (IL-6R) in its membrane-bound and soluble forms 12 , to down-modulate inflammation, and thus to avoid respiratory and multi-organ dysfunction. These studies have shown varied results that range from a lack of effect on mortality, time to clinical improvement, laboratory parameters and/or prevention of progression to a more severe disease 13 – 16 , to success in the modulation of some or all of these parameters in moderately 17 , severely 18 22 , and/or critically-ill patients 23 25 .…”
Section: Introductionmentioning
confidence: 99%